1998
DOI: 10.1136/ard.57.7.429
|View full text |Cite
|
Sign up to set email alerts
|

Ossification of the posterior longitudinal ligament in three geographically and genetically different populations of ankylosing spondylitis and other spondyloarthropathies

Abstract: , and abnormal SSEP (p=0.008). Group 2: 92% of 51 patients were men; the mean age was 30 years and the mean (SD) disease duration 11 (7) years. OPLL was reported in 15 (29%, 95%CI 17, 41) patients (nine AS, two psoriatic arthritis, three juvenile AS, and one Reiter's syndrome). Group 3: 95% of the 39 patients were men; the mean of age was 46 years and disease duration of 18 (10) years. OPLL was reported in nine (23%; 95%CI 10, 36) patients, including one with psoriatic arthritis, and two with Crohn's disease. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…54, 108 Resnick et al 109 found OPLL in 50% of patients with DISH. In 2009, Kawabori et al 51 reported a rare case of DISH with continuous-type OPLL at C2-4 that presented with cervical myelopathy from C-1 posterior tubercle impingement.…”
mentioning
confidence: 99%
“…54, 108 Resnick et al 109 found OPLL in 50% of patients with DISH. In 2009, Kawabori et al 51 reported a rare case of DISH with continuous-type OPLL at C2-4 that presented with cervical myelopathy from C-1 posterior tubercle impingement.…”
mentioning
confidence: 99%
“…The inflammation resulting from incarceration of the cord [20] may also cause the increased thickness of dorsal arachnoid [17,21,22]. In addition, within several mechanisms suggested as cause of nervous system involvement in AS, inflammation and compression are the main causative mechanisms [23,24]. It has been illustrated in AS patients that the neurologic deficit might be caused by inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Pathophysiology of SSEP abnormalities is unknown; also it was recommended that caution should be exercised in interpreting delayed evoked potentials if multiple sclerosis is suspected in a patient with AS [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Somatosensory evoked potentials were abnormal in 19 (63%) patients, and 9 patients (30%) had impaired function on brainstem auditory evoked potentials. Ramos-Remus et al [13] also reported abnormal SSEP findings in only 14.6% of their patients with AS.…”
Section: Introductionmentioning
confidence: 97%